The Influence of Sharia Financial Literacy and Customer Trust on Interest in Using Sharia Fintech in NTB - Fadillah, Nur; Ariani, Zaenafi; Hulaimi, Ahmad (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2026)
This study aims to analyze the effect of Islamic financial literacy and customer trust on the interest in using Islamic fintech in West Nusa Tenggara (NTB). This study was conducted to fill the gap in previous studies, which mostly focused on the interest in using digital services without examining actual financial behavior, such as saving in Islamic banks. The research uses a quantitative approach with a survey method of 122 respondents selected purposively. Data were collected through a Likert scale-based questionnaire and analyzed using multiple linear regression after classical assumption tests were conducted to ensure the model's feasibility. The results show that Islamic financial literacy has a positive and significant effect on interest in using Islamic fintech, while customer trust also strengthens interest in usage, although its contribution is smaller. Simultaneously, both variables are able to explain 73.2% of the variation in respondents' interest in Islamic fintech services. These findings emphasize the importance of improving Islamic financial education and strengthening public trust in Islamic-based digital financial institutions as a strategy to expand financial inclusion in the digital era. This study also provides direction for the development of Islamic fintech products and marketing strategies that are relevant to the characteristics of the younger generation as the dominant users.